2021
DOI: 10.1186/s12955-021-01724-w
|View full text |Cite
|
Sign up to set email alerts
|

Does patient engagement affect IBD patients’ health-related quality of life? Findings from a cross-sectional study among people with inflammatory bowel diseases

Abstract: Background Patients diagnosed with inflammatory bowel disease (IBD) are required to deal with the unpredictability of this clinical condition, which is associated with poorer health-related quality of life (HRQoL) compared to other clinical conditions. Patient engagement is currently demonstrated to relate with chronic patients’ HRQoL, but few studies have been conducted among this population. Methods A cross-sectional study was conducted among 117… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
1
15
1
Order By: Relevance
“…Assessing patient health engagement levels and implementing appropriate measures can improve healthcare delivery and encourage active patient participation in the care process (Barello et al., 2021). While there is no single approach to patient engagement, there are numerous strategies that healthcare providers can employ to ensure patients’ engagement in their healthcare management and access to health information, thereby improving their overall health status (Street et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing patient health engagement levels and implementing appropriate measures can improve healthcare delivery and encourage active patient participation in the care process (Barello et al., 2021). While there is no single approach to patient engagement, there are numerous strategies that healthcare providers can employ to ensure patients’ engagement in their healthcare management and access to health information, thereby improving their overall health status (Street et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing patient health engagement levels and implementing appropriate measures can improve healthcare delivery and encourage active patient participation in the care process (Barello et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of patient-centred care and patient engagement in routine practices is expected to improve patient outcomes by increasing self-management ability [15], treatment adherence [16], preventive behaviours [17,18], participation in shared decision making [19], satisfaction with care [20], and improving overall quality of life [21,22]. Moreover, many studies reported notable effects of a patient-centred approach to care on improvement in various patient-level outcomes such as distress, functioning, physiologic measures (e.g., blood pressure) and health service utilisation [23,24].…”
Section: The Bright Side Of Patient Centredness: the Values And Value Impliedmentioning
confidence: 99%
“…Research indicates that burnout is highly associated with long-term workload and stress of conscience. Patient-centred care seems to relieve staff's stress of conscience, as healthcare practitioners are enabled to provide appropriate care [22].…”
Section: The Bright Side Of Patient Centredness: the Values And Value Impliedmentioning
confidence: 99%
“…Conversely, a more engaged patient has been identified as less distressed in response to a perceived risk or sudden change ( 14 ) and more capable of managing his own health ( 15 ), which are aspects particularly challenged by this pandemic. In particular, previous studies revealed that a higher level of patient engagement promotes important outcomes for IBD patients, such as an increased health-related quality of life ( 16 ), and has been proposed as an important ingredient to promote IBD patients' psychosocial wellbeing ( 17 ). Finally, a more engaged patient has been found to better cope with negative emotions and panic, even during quarantine ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%